MOTOR SKILL AND PERFORMANCE SCHOLAR WRITING TASKS ON CHILDREN FROM 6 TO 11 YEARS OLD - Silva , Nadja Moreira da (2021)
Learning difficulties are present in classrooms and can cause irreparable damage such as dropping out of school. Studies show that individuals with learning difficulties tend to have delays in manual coordination, manual dexterity and fine motor skills. The objective of this study was to correlate the performance in tests of manual dexterity with the performance in school tasks of writing in children with typical development. The participants were 15 schoolchildren with typical development, between 6 and 11 years old, who attended regular school, being evaluated with the following instruments: Van Strien questionnaire for manual preference, Box and Blocks Test (TCB), Jebsen Taylor Manual Function Test (TFMJT) and School Performance Test (TDE). In the statistical analysis it was found that 84.62% of the children were characterized as right-handed and 15.38% as ambidextrous, in addition to a positive linear correlation between TCB and TDE, and a negative linear correlation between TFMJT and TDE, and that children performed better according raising of the age. It was concluded that there was a correlation between manual motor dexterity and performance in school writing tasks.